2016
DOI: 10.1039/c6nr06745j
|View full text |Cite
|
Sign up to set email alerts
|

2D DNA lattices constructed from two-tile DAE-O systems possessing circular central strands

Abstract: We reported a classical two-tile system of DAE-O (doublecrossover, antiparallel, and even half-turns tiles with odd half-turns connection) to construct regular single crystalline 2D (two dimensional) DNA lattices, using pre-circularised oligonucleotides of 42-, 64-, and 84-nt (nucleotides) as the central looped strands in DAE tiles respectively. DAE tiles with 42- and 64-nt as central strands, either in circular form or in linear form, grew regular single crystalline lattices well. However DAE tiles including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The previously reported circular DAE is structurally similar to a linear DAE, with a negligible difference: the former has a continuous circular scaffold, whereas the latter has a looped scaffold carrying a nick . What about building a DAO tile from a small circular strand?…”
Section: Figurementioning
confidence: 91%
“…The previously reported circular DAE is structurally similar to a linear DAE, with a negligible difference: the former has a continuous circular scaffold, whereas the latter has a looped scaffold carrying a nick . What about building a DAO tile from a small circular strand?…”
Section: Figurementioning
confidence: 91%
“…2 DNA nanotechnology can be mainly divided into two categories: structural DNA nanotechnology and dynamic DNA nanotechnology, in which DNA strands are employed to program the spatial and temporal distribution of matter. 3 Based on 'bottom-up' engineering approaches, structural DNA nanotechnology has realized the fabrication of 2D and 3D DNA assemblies with various sizes and spatial structures, such as DNA lattices, 4,5 DNA origami, 6 DNA tetrahedron structures, [7][8][9] DNA nanotubes 10,11 and so on. Unlike structural DNA nanotechnology, dynamic DNA nanotechnology lays emphasis on the non-equilibrium dynamics, in which the formation of DNA nanostructures results from successive dynamic assembly of DNA motifs.…”
Section: Introductionmentioning
confidence: 99%
“…Among DNA operations in nature, DNA looping, causing twisting, bending, torsion, curving, kinking, stressing, and disruption of DNA molecules, has very important physiological functions, such as regulating transcription or facilitating protein‐DNA assembly during replication, recombination, condensation, etc . Instead of using the most common linear strands as the beginning molecules to self‐assemble 1D, 2D, and 3D nanostructures, recently we applied pre‐circularised oligonucleotides to successfully build homogeneous nanotubes by stacking lateral duplex rings and to construct 2D lattices in the longitudinal direction of double helices, suggesting the good stability and rigidity of motifs involving at least one pre‐circularised DNA strand …”
Section: Figurementioning
confidence: 99%
“…[21,22] Instead of using the most common linear strands as the beginning molecules to self-assemble 1D, 2D, and 3D nanostructures, recently we applied pre-circularised oligonucleotides to successfullyb uild homogeneous nanotubes by stacking lateral duplex rings and to construct 2D latticesi nt he longitudinal direction of doubleh elices, suggestingt he good stabilitya nd rigidity of motifs involving at least one pre-circularised DNA strand. [23][24][25][26] Seeman and his colleaguesi nvestigated the three-way junction and four-wayj unction (Holliday Junction) structures in the early years. They indicated that the three-way DNA junction structures are conformationally flexible, while the double crossover structuresa re more rigid components that are needed to assemblel arge and shapable periodic lattices.…”
mentioning
confidence: 99%